2011
DOI: 10.4049/jimmunol.1100231
|View full text |Cite
|
Sign up to set email alerts
|

Insulinoma-Released Exosomes or Microparticles Are Immunostimulatory and Can Activate Autoreactive T Cells Spontaneously Developed in Nonobese Diabetic Mice

Abstract: Exosomes (EXO) are secreted intracellular microparticles that can trigger inflammation and induce antigen-specific immune responses. To test possible roles of EXO in autoimmunity, we isolated small microparticles, mainly EXO, from mouse insulinoma and examined their activities to stimulate the autoimmune responses in non-obese diabetic (NOD) mice, a model for human type 1 diabetes. We demonstrate that the EXO contains strong innate stimuli and expresses candidate diabetes autoantigens. They can induce secretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(126 citation statements)
references
References 61 publications
2
114
0
Order By: Relevance
“…Exosomes from the Min6 mouse insulinoma cell-line have been shown to contain antigens that trigger autoimmunity in NOD mice. 10 In preliminary mouse experiments, we did not detect an in vivo immune effect in BALB/c mice after injection of EVs purified from leukoreduced RBC units from C57BL/6 mice (supplemental Figure 3), potentially due to limitations of the mouse model in recapitulating the human system. Of note, in our human experiments, the immune effect did not appear to be antigen specific, as EV stimulatory capacity did not differ when EVs were derived from autologous vs allogeneic cells.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Exosomes from the Min6 mouse insulinoma cell-line have been shown to contain antigens that trigger autoimmunity in NOD mice. 10 In preliminary mouse experiments, we did not detect an in vivo immune effect in BALB/c mice after injection of EVs purified from leukoreduced RBC units from C57BL/6 mice (supplemental Figure 3), potentially due to limitations of the mouse model in recapitulating the human system. Of note, in our human experiments, the immune effect did not appear to be antigen specific, as EV stimulatory capacity did not differ when EVs were derived from autologous vs allogeneic cells.…”
Section: Discussionmentioning
confidence: 87%
“…6 However, exosomes bearing autoimmune antigens are immunostimulatory in a NOD mouse model of diabetes, leading to production of proinflammatory cytokines and proliferation of T cells. 10 In this article we examine the role of EVs in potentially mediating an immune modulatory effect associated with blood transfusion. It is believed that transfusion of fresh blood may carry less risk of adverse reactions compared with old blood, attributed to a red blood cell (RBC) "storage lesion," which has been described as physical and chemical changes of RBCs during the time of storage.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes isolated from mouse insulinoma induce the secretion of inflammatory cytokines including IL-6 and TNF-␣ in splenocytes cultured from nonobese diabetic mice (34). Studies using microvascular endothelial cells (HMEC-1) as an exosome source demonstrated that stress conditions (such as hypoxia, glucose, and TNF-␣) can alter exosomal protein and mRNA composition (35).…”
Section: Exosome-induced Cytokine Releasementioning
confidence: 98%
“…The transfer of miRNAs and siRNAs can also alter protein expression in target cells by binding to complementary mRNA in the cytoplasm, inhibiting translation (Guay et al 2015, Lee et al 2015b. Intercellular transfer of exosomal cargo has been implicated in immunomodulation, initiation of cellular proliferation, angiogenesis, regulation of apoptosis, platelet activation and other phenotypic alterations in targeted cells (Rak 2010, Sheng et al 2011, Corrado et al 2013, Tomasoni et al 2013, Rahman et al 2014, Shabbir et al 2015. Such alterations have been associated with both healthy and pathogenic cellular behaviors (BenitoMartin et al 2015, Ciardiello et al 2016.…”
Section: Exosomes As Vehicles For Cell-cell Communicationmentioning
confidence: 99%